Investigation of extrusion limit of Incoloy028 alloy tube by combining numerical and analytical methods. Issue 1 (March 2016) - Sun, C.; Liu, D.; Fu, M.; Yang, J.
Abstract Extrusion limit is an important evaluation criterion in extrusion process design as it determines the deformation degree in each operation. In this paper, a new method for establishment of extrusion limit diagram was proposed. To do so, the constitutive equation of Incoloy028 alloy (IN028) was established by hot compression test and the tube hot extrusion process was simulated by commercial Deform-2D software. In addition, the extrusion process is also analyzed by analytical method in which the billet heating temperature, extrusion speed and ratio were considered as influence factors. The analytical results of extrusion force and demoulding temperature were obtained. The maximum extrusion pressure of 60 MN and the eutectic melting temperature of IN028 (1, 350 °C) was selected as the limit of extrusion force and the permissible maximum temperature. The limit diagram for IN028 tube in hot extrusion process were generated using the analytical and numerical methods simultaneously and the extrusion limit diagram of IN028 at different ratios is thus provided.